Toward a Fundamental Understanding of the Role of Lignin in the Biorefinery Process - Yao, Lan; Yang, Haitao; Meng, Xianzhi; Ragauskas, Arthur J. (Frontiers in Energy Research, 2022)
As one of the main components in biomass, lignin plays a vital role in the biorefinery industry. Its unique structural feature increases the dose of cellulases during enzymatic deconstruction and is an attractive resource for many high valued products. The inhibition of lignin on cellulases is proposed to occur in several ways, with the most studied being nonproductive enzyme binding, which is attributed to hydrogen bonding, hydrophobic and/or electrostatic interactions. This review provides a comprehensive review of how lignin is transformed during various pretreatment methods as well as how these changes impact the cellulases inhibition. Future pretreatment directions for decreased cellulases inhibition are also proposed.